Template-assisted synthesis of ruthenium oxide nanoneedles: electrical and electrochemical properties - Subhramannia, Mahima; Balan, Beena K.; Sathe, Bhaskar R.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2007)
We here demonstrate the formation of bundles of RuO2 nanoneedles (ca. 100 nm diameter) by a templateassisted electrodeposition from aqueous RuCl3 solution under potentiostatic conditions at room temperature. Cyclic voltammetric measurements in 0.5 M H2SO4 show significantly higher redox-related charging behavior for the RuO2 nanoneedles compared to that of the commercial sample, which is also supported by the electrochemical impedance data. A comparison of the specific capacitance reveals a higher value for nanoneedles (3 F/g instead of 0.4 F/g for the bulk), which has been explained on the basis of enhanced reactivity. More interestingly, electrical transport measurements reveal a transition from metallic to semiconducting behavior especially at low-temperature caused by an impurity scattering mechanism. We anticipate that the present simple route for the fabrication of RuO2 nanostructures will be useful to exploit their potentials in various fields such as electrocatalysis, nanoelectronics, and more importantly for designing supercapacitors.

Tuning the transport properties of Poly(oxyethylene)bisamine - Nafion polyelectrolyte complexes by dielectric manipulation - Parthasarathy, Meera; Kakade, Bhalchandra A.; Pillai, Vijayamohanan K. (Macromolecules, 2008)
Polyelectrolyte complexes (PECs) of Nafion-H+, a perfluorosulfonic acid ionomer, and Poly(oxyethylene)bisamine (Polyox) were synthesized, and the effect of electrostatic interactions on the physicochemical properties of the individual components was studied using a combination of spectroscopic and electrochemical techniques. More specifically, the pristine PECs were extensively characterized using viscosity, surface tension, and pH measurements and diffuse reflectance Fourier transform infrared (DRIFT) spectroscopy and their transport properties were investigated using cyclic voltammetry and electrochemical impedance spectroscopy, by employing [Fe(CN)(6)](3-) as a redox probe. Acid-base interaction between Nafion and Polyox is evident from pH measurements of the blend solutions, which indicate salt formation at a 50:50 composition, supported further by the existence of a maximum in the plot of surface tension versus blend composition. DRIFT spectra of the PEC membranes indicate subtle changes in the ionic environment and a transition from a state of medium hydration to a partially dehydrated state of the parent ionomer, Nation, after complexation with Polyox. Further evidence for polyelectrolyte-polyelectrolyte association is obtained from cyclic voltammetry, which shows that the interaction between the redox active chromophore, [Fe(CN)(6)](3-), and the pendent sulfonate groups of Nafion is minimized by complexation with the oppositely charged polyelectrolyte Polyox. The water-soluble nature of these PECs along with the tunable range of properties with blend composition could qualify them as suitable candidates for developing stimuli-responsive polymer systems for pharmaceutical and environmental applications.

Tuning the wetting properties of multiwalled carbon nanotubes by surface functionalization - Kakade, Bhalchandra A.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2008)
A simple strategy of chemical functionalization is employed here for controlling the wettability of multiwalled carbon nanotube films from superhydorphobic (156 degrees) to nearly hydrophilic (40 degrees), which further shows superhydrophilicity with a water contact angle of about 0 degrees within 2 s. The hydrophobic surface (water contact angle 145 degrees) in case of nitric-acid-treated MWCNT bucky paper shows an unusual pinning action even at a tilt angle of 45 degrees, following Wenzel behavior of the surface. The variation in the wetting properties of MWCNT bucky paper using such surface designing strategies provides controlled heterogeneity on the surface with no or minimal effect on surface roughness.

Thiolated graphene - a new platform for anchoring CdSe quantum dots for hybrid heterostructures - Debgupta, Joyashish; Pillai, Vijayamohanan K. (Nanoscale, 2013)
Effective organization of small CdSe quantum dots on graphene sheets has been achieved by a simple solution exchange with thiol terminated graphene prepared by diazonium salt chemistry. This generic methodology of CdSe QD attachment to any graphene surface has remarkable implications in designing hybrid heterostructures.